2013
DOI: 10.2478/s13380-013-0128-z
|View full text |Cite
|
Sign up to set email alerts
|

microRNA s (9, 138, 181A, 221, and 222) and mesial temporal lobe epilepsy in developing brains

Abstract: Background: Recently, microRNAs (miRNAs) have attracted much attention as novel players in the pathogenesis of mesial temporal lobe epilepsy (MTLE) in mature and developing brains. This study aimed to investigate the expression dynamics of miR-9, miR-138, miR-181a, miR-221, and miR-222 in the hippocampus of an immature rat model during the three stages of MTLE development and in children with MTLE. Methodology: qPCR was used to measure expression levels during the three stages of MTLE development (2 h, 3, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 35 publications
(32 reference statements)
1
10
0
Order By: Relevance
“…In the intervening years, six studies have undertaken the miRNA expression profiling either in brain tissue samples (Kan et al, 2012 ; McKiernan et al, 2012b ; Kaalund et al, 2014 ; Zucchini et al, 2014 ) or serum (Wang et al, 2015a , b ) of patients with epilepsy (Table 2 ), along with study on individual miRNAs in human epilepsy (Aronica et al, 2010 ; Jimenez-Mateos et al, 2012 ; Omran et al, 2012 ; Ashhab et al, 2013a , b ; Peng et al, 2013 ; Alsharafi and Xiao, 2015 ). Specifically, miRNAs expression profiles were performed on patients with mesial temporal lobe epilepsy (mTLE) (Kan et al, 2012 ; Kaalund et al, 2014 ), temporal lobe epilepsy (TLE) (McKiernan et al, 2012b ), or Drug-resistant epilepsy (Zucchini et al, 2014 ; Wang et al, 2015b ).…”
Section: Mirna Alterations In Epilepsymentioning
confidence: 99%
See 2 more Smart Citations
“…In the intervening years, six studies have undertaken the miRNA expression profiling either in brain tissue samples (Kan et al, 2012 ; McKiernan et al, 2012b ; Kaalund et al, 2014 ; Zucchini et al, 2014 ) or serum (Wang et al, 2015a , b ) of patients with epilepsy (Table 2 ), along with study on individual miRNAs in human epilepsy (Aronica et al, 2010 ; Jimenez-Mateos et al, 2012 ; Omran et al, 2012 ; Ashhab et al, 2013a , b ; Peng et al, 2013 ; Alsharafi and Xiao, 2015 ). Specifically, miRNAs expression profiles were performed on patients with mesial temporal lobe epilepsy (mTLE) (Kan et al, 2012 ; Kaalund et al, 2014 ), temporal lobe epilepsy (TLE) (McKiernan et al, 2012b ), or Drug-resistant epilepsy (Zucchini et al, 2014 ; Wang et al, 2015b ).…”
Section: Mirna Alterations In Epilepsymentioning
confidence: 99%
“…In 2013, Ashhab and colleagues aimed to explore the dynamic expression of miR-221 and miR-222 in the three phases of TLE and in children with TLE. They demonstrated that both miR-221 and miR-222 were downregulated in the three phases of TLE in animal models and in children with epilepsy (Ashhab et al, 2013a ). In the same study, inflammation-related miR-138 was decreased in the seizure-related phase but not in the latent phase, whereas inflammation-related miR-181a was decreased in the acute phase, normal in the latent phase and increased in the chronic phase (Ashhab et al, 2013a ).…”
Section: Therapeutic Aspects Of Mirnasmentioning
confidence: 99%
See 1 more Smart Citation
“…miR-138 is a neuronspecific miRNA, which dynamically regulates neural development by controlling the shape and size of dendrites and thereby influences long-term memory [24]. miR-138 was also found to be downregulated in the seizure-related stages of the mesial temporal lobe epilepsy (MTLE) model in the developing brains [10]. [14].…”
Section: Discussionmentioning
confidence: 97%
“…miRNAs are also involved in the regulation of several aspects of the innate, adaptive immune responses and inflammationrelated disorders. Studies uncovered a subset of miRNAs which are brain-enriched including miRNAs (124, 134, 9, and 138) and inflammationrelated miRNAs including (132, 181a, 221, and 222) which were extensively studied in multiple brain disease in both developing and adult brains [4,[10][11][12], and also in infectious diseases [13][14][15].…”
Section: Introductionmentioning
confidence: 99%